Precision chemical heating for diagnostic devices. Issue 23 (27th October 2015) - Buser, J. R.; Diesburg, S.; Singleton, J.; Guelig, D.; Bishop, J. D.; Zentner, C.; Burton, R.; LaBarre, P.; Yager, P.; Weigl, B. H.
Abstract : A complete design strategy for electricity-free heaters compatible with isothermal nucleic acid amplification is described. Abstract : Decoupling nucleic acid amplification assays from infrastructure requirements such as grid electricity is critical for providing effective diagnosis and treatment at the point of care in low-resource settings. Here, we outline a complete strategy for the design of electricity-free precision heaters compatible with medical diagnostic applications requiring isothermal conditions, including nucleic acid amplification and lysis. Low-cost, highly energy dense components with better end-of-life disposal options than conventional batteries are proposed as an alternative to conventional heating methods to satisfy the unique needs of point of care use.